PEMBERDAYAAN EKONOMI KREATIF, PEMUDA DAN OLAHRAGA DI DESA LUBUK TENAM - Yahfenel Evi Fussalam; Ridho Kurniawan; Deka Ismi Mori Saputra; Aprizan Aprizan; Zulmi Zulmi (LP3M STKIP MUHAMMADIYAH MUARA BUNGO, 2020)
The potential of biological wealth and diversity of ecosystems which are natural resources that are thankful for. However, the empowerment of human resources, especially youth, as the next generation, is no less important than the anticipation of people's dependence on future natural resources. Therefore community service activities in the village of Lubuk Tenam Jujuhan Ilir, Bungo Regency are aimed at empowering the creative economy, youth and sports. The activity is carried out in three stages; 1) collaborating with partners, 2) Introduction to the concepts of youth, sports management, and entrepreneurs, 3) practice, 4) evaluation. The results of this activity indicate that: First, youth enthusiastically participated in entrepreneurship activities, Second, participants felt the benefits of introducing the concept of youth religuises and website management. Third, the village government gave a positive response to the socialization of sports management activities, especially in terms of managing sports facilities and infrastructure